Analysis Factors Influencing Economic Growth, Unemployment and Poverty in Indonesia - Imda Safitri; Moehadi Moehadi; Joko Hadi Susilo; Endang Endang (Universitas Negeri Semarang, 2023)
This research was conducted on the basis of several problems that occurred in Indonesia, namely, the lack of economic resilience and the impact of the global crisis, which can affect uneven levels of economic growth, unemployment caused by a mismatch between labor skills and labor market demand, and can lead to poverty due to income inequality. The purpose of this research is to determine the characteristics of the variables that influence economic growth, unemployment and poverty in Indonesia. This research will later discuss the simultaneous model relationship between variables that affect economic growth, unemployment, and poverty using the Three Stage Least Square (3SLS) method. The research object consists of 34 provinces in Indonesia in the period 2012-2021. The research results showthe unemployment, inflation, and investment variables have a significant positive effect on economic growth which has a probability value of less than 0.05 and a positive coefficient value, while the human development index variable has a prob value. less than 0.05 and the coefficient is negative so it has a significant negative effect. The results of the second equation, the Human Development Index and economic growth have a significant effect on the prob value. 0.00 0.05, while labor has a significant negative impact with a prob value. 0.05 and the coefficient is negative, while the poverty variable has a prob value. 0.06 0.05 so it has no significant effect on unemployment. Analysis of the results of the third equation reveals that poverty is significantly affected by the gini ratio with the prob value. 0.00, but not affected by unemployment or the minimum wage because the probability value is more than 0.05.